Psychosis in a 15-Year-Old Female with Herpes Simplex Encephalitis in a Background of Mannose-Binding Lecithin Deficiency - Kenneth Asogwa; Kwame Buabeng; Amarjit Kaur (Case Reports in Psychiatry)
Historically, psychotic disorder has been associated with viral infection. Herpes simplex infections and Epstein-Barr virus (EBV) among other viral infections have been implicated in psychotic disorder. Of note in this case report is psychotic disorder that occurred following reactivation of herpes simplex infection in a background of mannose-binding lecithin (MBL) deficiency, childhood EBV infection, and severe psychosocial stress. Herpes simplex encephalitis (HSE) remains a significant cause of morbidity and mortality despite advancement in its treatment with intravenous acyclovir. Many studies have reported psychiatric and neurological manifestation of herpes simplex infection following primary or reactivated infection, while others suggest milder clinical course of herpes simplex encephalitis in a background of immunosuppression. Another contributory factor to psychotic disorder in this case is childhood EBV exposure which has been reported to increase the risk of psychosis in adolescence and adulthood. This case report describes a 15-year-old female with MBL deficiency who presented with psychosis caused by reactivated herpes simplex infection and had good clinical recovery. Based on childhood Epstein-Barr virus exposure and psychosis in adolescence (current case), she is at increased risk of psychotic disorder in adulthood, which underscores the importance of long-term monitoring.